Teaching Individuals with Down Syndrome and Moderate or Severe Intellectual Disability with The Aim of Their Acquiring, Retaining and Recalling Knowledge: An Intervention Programme for Discovering and Understanding The Environment - Christina S Lappa; Constantinos N Mantzikos (International Journal of Pedagogy and Teacher Education, 2021)
Three adults with Down syndrome (DS, hereafter) and moderate or severe intellectual disability were taught the growth stages of wheat (cultivation, tillage, threshing), the products that are derived from it and how this staple human food grain is produced, with the aim of their acquiring knowledge, retaining it and being able to recall it from memory. A quasi-experimental baseline design was implemented. The participants were taught using questions and images, and their answers were examined and re-examined after withdrawing the initial training tools (questions and images) in order to show whether they were able to acquire, retain and recall the knowledge. The intervention programme lasted two months. In order to check the effectiveness of the intervention and the maintenance of the new information, as well as to draw the respective conclusions, evaluations were carried out before the intervention, immediately after it and two weeks after its completion. The results showed that the three participants acquired knowledge about the growth stages of wheat, its products and this staple human food, they retained that knowledge and were able to recall and narrate it in two subsequent probes conducted one and two weeks after the initial probe without the help of questions and images. The results of this intervention show that individuals with DS and moderate or severe intellectual disability can be educated and acquire knowledge, as well as retain and recall it. An additional important finding is that repeated recalling of knowledge promotes long-term retention.